Ceramic behavior of ball clay with gadolinium oxide (Gd2O3) addition - Hernández, Maria Florencia (2017)
The effect of the addition of gadolinium oxide (Gd2O3) in the thermal behavior of a (66%) kaolinitic ball clay was studied and compared with the pure clay. The incorporation of Gd2O3 is of technological interest for the design of smart ceramic proppants used for unconventional gas and oil well stimulation. This proppant material is used to obtain important information, such as the location and height of the created hydraulic fractures. The studied comprised a set of thermal analysis up to 1400 °C and the sintering behavior of the clay, up to 5% addition. The developed texture and microstructure was also assessed. No important effects in kaolinite dehydration temperature and mullites (primary and secondary) formation were observed (500–600 and 990 °C). The sintering range of the studied clay is 1080–1360 °C; the 5% wt. addition resulted in 80 °C decrease of the final sintering temperature. Mixtures fired at 1250 and 1400 °C resulted in dense ceramic materials with mullite as principal crystalline phase accompanied by quartz and cristobalite; imbibed in a viscous glassy phase which was proportionally increased by the added oxide. The mullite content and cell parameters were not affected. No gadolinium containing binary or ternary crystalline phases were detected, inferring that the rare earth is dissolved by the active viscous glassy phase thermally formed from the clay crystalline phases. Low concentration addition of the oxide did not affect the porosity or water absorption of the developed ceramics. Only the 5% wt. addition resulted in a slightly higher de-sinterization with the appearance of macro-porosity if fired at 1400 °C.